Implementasi Pelayanan Administrasi Kependudukan Kota Malang - Suko Wahyono; Budi Prihatminingtyas; Annisa Purwatiningsih (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2019)
Policy implementation is a government action in regulating and taking care ofpeople's needs in various affairs including fulfilling basic population services for thecommunity. The purpose of this paper is to analyze the implementation of basic populationservices at the Malang City Population and Civil Registration Service. The research methodusing qualitative descriptive shows that the services of family cards and identity cards according to the Community Satisfaction Survey are very good results. Meanwhile the resultsof the implementation according to Edward III aspects of communication have gone wellthrough the process of communication between the service staff and the community. Resourceaspects experience barriers to human resources of high school graduates and some areelderly. The capacity of internet service networks is still not optimal and wasteful of thebudget because all services are not online systems. The aspect of disposition, gives an attitudeto the apparatus that with the provision of incentives and benefits they are able to carry outservices that are not from the community. This is due to the formulation of this policy throughthe government institutions of the city of Malang so that they must be able to carry out theirduties as well as possible. Aspects of the Bureaucratic Structure, provide Standard OperatingProcedures (SOP) as guidelines for the duties and functions of the apparatus in serving thecommunity. for this reason, good service is needed by paying attention to aspects of humanresources and facilities that support the effectiveness of population services at the MalangCity Population and Civil Registration Service Keywords: Implementation, Public Policy, BasicPopulation Services.